2022
DOI: 10.2215/cjn.07620621
|View full text |Cite
|
Sign up to set email alerts
|

Waiting Time for Second Kidney Transplantation and Mortality

Abstract: Background and objectivesThe median kidney transplant half-life is 10–15 years. Because of the scarcity of donor organs and immunologic sensitization of candidates for retransplantation, there is a need for quantitative information on if and when a second transplantation is no longer associated with a lower risk of mortality compared with waitlisted patients treated by dialysis. Therefore, we investigated the association of time on waiting list with patient survival in patients who received a second transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 28 publications
0
21
0
1
Order By: Relevance
“…Despite this fact, after the first kidney graft failure, we observed that the probability to receive a second KT is similar to dying. Patients from our cohort were quite older (∼10 years) compared with other studies [ 7 , 15 ]. It is well-known that mortality in patients requiring dialysis after kidney graft loss is higher than in transplant-naïve peers [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Despite this fact, after the first kidney graft failure, we observed that the probability to receive a second KT is similar to dying. Patients from our cohort were quite older (∼10 years) compared with other studies [ 7 , 15 ]. It is well-known that mortality in patients requiring dialysis after kidney graft loss is higher than in transplant-naïve peers [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 76%
“…When living donor KT is not feasible, preemptive deceased-donor kidney retransplantation represents the optimal therapy for patients who lose kidney allograft, exhibiting greater patient and graft survival, thanks to avoiding the morbidity and mortality associated with dialysis reinitiation [ 3 , 15 , 20 ]. However, this option is not always possible due to patient comorbidities or limited because of HLA sensitization, or by the fact that time on dialysis is a relevant criterion in our allocation score.…”
Section: Discussionmentioning
confidence: 99%
“…It is demonstrated that KT provides superior life expectancy [61][62][63] and QoL [64][65][66] than dialysis. Nonetheless, returning to dialysis after a failed transplant entails a greater risk of death than starting RRT for the first time [11,40,43,67,68]. Therefore, preserving graft function as much as possible is vital for long-term patient survival.…”
Section: Post-transplant Recipient and Allograft Survivalsmentioning
confidence: 99%
“…Ideally, a pre-emptive strategy should be adopted to ensure the best results [6][7][8][9]. However, due to the scarcity of donors, the vast majority of transplant candidates require prolonged periods of renal replacement therapy (RRT) before receiving a suitable organ [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the benefits of retransplantation, the 2014 British Transplant Society Guidelines for the Management of the Failing Kidney Transplant, recommend that patients suitable for retransplant should be evaluated when graft failure is anticipated within one year, and ideally provide preemptive retransplantation [ 31 ]. Timely relisting is particularly important since recently published data showed that the survival benefit of retransplantation diminishes with longer waitlist times [ 32 , 33 ].…”
Section: The Benefits Of Retransplantationmentioning
confidence: 99%